The Effect of PVP Molecular Weight on Dissolution Behavior and Physicochemical Characterization of Glycyrrhetinic Acid Solid Dispersions - Xiaoyu Sui; Yan Chu; Jie Zhang; Honglian Zhang; Huiyu Wang; Tingting Liu; Cuiyan Han (Advances in Polymer Technology)
The effect of polyvinylpyrrolidone (PVP) as glycyrrhetic acid (GA) solid dispersions carrier at different molecular weights on the dissolution behavior and physicochemical properties was investigated. PVP-GA-SDs prepared with all four molecular weight PVPs displayed good enhancement of dissolution rate and equilibrium solubility compared with pure drug and corresponding physical mixtures. The results showed that the enhancement effect of molecular weight on dissolution rate and equilibrium solubility follows PVP K30>PVP K60>PVP K17>PVP K15. In addition, the dissolution rate and solubility of the SDs with a carrier-drug ratio of 8 : 1 were better than the samples of 4 : 1. The DSC and XRD patterns showed that the crystallization of GA in SDs prepared by PVP K30 and PVP K60 was significantly inhibited, and both were transformed to amorphous. Based on FTIR and Raman detection, a hydrogen-bond between PVP and drug molecules is formed. SEM results showed that there were no significant differences in the appearance of SDs prepared with four PVPs, and no crystalline morphology of GA was seen. In conclusion, the findings of this study demonstrated that the dissolution performance of the PVP-GA-SDs prepared by the solvent method is related to the molecular weight of PVP, and the change in the molecular weight of PVP does not cause a monotonic change in dissolution of GA. The samples with PVP K30 as the carrier have the best dissolution performance.